Indirect hemagglutination test for human antibody to typhus and spotted fever group rickettsiae. - Shirai, A (1975)
An indirect hemagglutination (IHA) test is described that uses glutaraldehyde-stabilized erythrocytes treated with a rickettsial erythrocyte-sensitizing substance obtained from Rickettsia typhi or Rickettsia rickettsii. The serological reagent was stable for at least 3 months at room temperature and 6 months at 4 C. It exhibited group specificity and no group cross-reactivity. At a minimum dilution of 1:40, acute and early convalescent epidemic and murine typhus antisera showed 86% positive reactors, whereas similar spotted fever antisera had 74% positive reactors. In comparison with the indirect fluorescent antibody test, the IHA procedure gave lower titers but showed comparable detection of seroconversion with most paired sera. The IHA test demonstrated significantly higher titers than the complement fixation test and was more sensitive than either the complement fixation or Weil-Felix test in identifying seroconversion. No agglutination was observed when sensitized erythrocytes were tested with rodent sera known to contain rickettsial antibodies.